Microbial succession and the functional potential during the fermentation of Chinese soy sauce brine - Sulaiman, Joanita; Gan, Han Ming; Yin, Wai-Fong; Chan, Kok-Gan (Frontiers in Microbiology, 2014)
The quality of traditional Chinese soy sauce is determined by microbial communities and their inter-related metabolic roles in the fermentation tank. In this study, traditional Chinese soy sauce brine samples were obtained periodically to monitor the transitions of the microbial population and functional properties during the six months of fermentation process. Whole genome shotgun (WGS) method revealed that the fermentation brine was dominated by the bacterial genus Weissella and later dominated by the fungal genus Candida. Metabolic reconstruction of the metagenome sequences demonstrated a characteristic profile of heterotrophic fermentation of proteins and carbohydrates. This was supported by the detection of ethanol with stable decrease of pH values. To the best of our knowledge, this is the first study that explores the temporal changes in microbial successions over a period of six months, through metagenome shotgun sequencing in traditional Chinese soy sauce fermentation and the biological processes therein.